Resident Attitudes on Ethical and Medical Decision-Making for Neonates at the Limit of Viability - Kukora, Stephanie; Laventhal, Naomi (American Journal of Perinatology, 2016)
Objective This study aims to identify pediatric resident knowledge and attitudes on current practices and ideal gestational age (GA) thresholds for offering and mandating resuscitation, and the role of influencing factors in decision-making.Study Design Pediatric residents were assessed via electronic survey at a large academic institution.Result A total of 62% of the residents identified 23 weeks as the lower threshold for resuscitation, despite 84 and 89% reporting that practices are inconsistent and unclear, respectively. Only 21% identified 24 weeks as the latest GA that parents may decline. The majority disagreed with our current practices, identifying older GA as appropriate for all thresholds. They reported scientific evidence as undervalued, and attending physicians' personal beliefs as overvalued in decision-making.Conclusion Our residents recognize decision-making for extremely preterm infants consistent with general guidelines for management based on population outcomes, but attribute these decisions to physicians' personal beliefs. Preferences for higher GA thresholds for resuscitation may reflect disproportionate pessimism about these patients or diverse values regarding autonomy.
Keywords: margin of viability; decision-making; resident; neonatal resuscitation; gestational age